7(x+3)-8x=11

Simple and best practice solution for 7(x+3)-8x=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(x+3)-8x=11 equation:


Simplifying
7(x + 3) + -8x = 11

Reorder the terms:
7(3 + x) + -8x = 11
(3 * 7 + x * 7) + -8x = 11
(21 + 7x) + -8x = 11

Combine like terms: 7x + -8x = -1x
21 + -1x = 11

Solving
21 + -1x = 11

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-21' to each side of the equation.
21 + -21 + -1x = 11 + -21

Combine like terms: 21 + -21 = 0
0 + -1x = 11 + -21
-1x = 11 + -21

Combine like terms: 11 + -21 = -10
-1x = -10

Divide each side by '-1'.
x = 10

Simplifying
x = 10

See similar equations:

| c(w-5)= | | 0.02p+0.07(1200-p)=70 | | -2(6m+7)= | | 8x^3-62x^2+43x-7=0 | | 7c-6=8c-11 | | (-3x+5)+(-8x+30)=90 | | 20x^3-25x=0 | | 2-4x=-2x+4 | | Log(7)0= | | 3(3+4x)=21 | | 42-8x=14+6x | | 108=-2(2+8v) | | 11x+9x=140 | | -9+-8(-9q+-8)= | | 7t-2t=20-4+9 | | -3x-6+9x=-4x+6 | | 4k+1+3k=-6 | | 6(2x+10)=72 | | 1.75+0.35=2.80 | | 3(1-2x)=-5(3x-2) | | 8x-4=19-3x | | 2(w+5)+2w=70 | | V=imh | | -3(x-6)=-3-3x | | 2(4v-6)-2v=-8+5v | | 4y-3y-1=8 | | 2x-8=2(x-5) | | 2(3x+5)+2(8)=112 | | 0.25p=30 | | -5=-7(x+3)-3x | | 91-(6x+15)=6(x+4)+x | | 7x+17-5x+17=6 |

Equations solver categories